Exercise physiology theory and application to fitness and performance - Powers, Scott K. (Scott Kline) 1950-; Howley, Edward T. 1943- (McGraw-Hill Create, 2011)
"Written especially for exercise science and physical education students, this text provides a solid foundation in theory illuminated by application and performance models to increase understanding and to help students apply what they've learned in the classroom and beyond. "-- Provided by publisher.